First Report of Gallbladder Volvulus Managed with a Robotic Approach - Roberto Bustos; Hassan Mashbari; Antonio Gangemi (Case Reports in Surgery)
Gallbladder volvulus (GV) is an axial twisting of the gallbladder (GB). If not treated on time, this condition has a mortality up to 6%. It is usually diagnosed intraoperatively, because it can mimic a typical acute cholecystitis. An 81-year-old female patient presented with an acute onset of right upper quadrant pain accompanied with nausea. The patient was admitted to receive treatment for acute cholecystitis after the findings of ultrasound imaging. Robotic-assisted cholecystectomy was the approach chosen. GV was diagnosed after initial diagnostic laparoscopy. Cholecystectomy was performed uneventfully. Indocyanine green fluorescence was used to assess the biliary anatomy. The postoperatory course went uneventful. The patient was discharged home on postoperatory day 2.